Understanding tax morale and its effect on individual taxpayer compliance - Pope, Jeffrey; McKerchar, M. (Sweet & Maxwell Limited, 2011)
Understanding individual taxpayer compliance behaviour continues to be a complex and challenging area for researchers and tax administrators alike. More recently there has been a shift in focus from seeking to understand why taxpayers do not comply with their tax obligations, to understanding why they do. This shift in focus has arisen because the observed level of taxpayer compliance by individuals is typically higher than that expected according to the traditional economic deterrence models. This unexpected gap between expected and actual levels of compliance is generally attributed in the literature to the phenomenon of “tax morale”. However, this phenomenon is somewhat elusive in many significant respects including its meaning and relevance in the context of individual taxpayer compliance; how it may be influenced and, of course, its effects. This article sets out to unravel some of the mystery surrounding tax morale by, first, critically reviewing the literature and then developing a conceptual model of tax morale that includes both its determinants and its likely effects. It is anticipated that this model can then be used to underpin further research that will result in a deeper understanding of individual taxpayer behaviour and, in turn, of how compliance may be more effectively improved.